北极航道法律地位研究 - 王丹维; WANG Danwei (《中国海洋法学评论》编辑部, 2011)
王丹维,所在单位:厦门大学法学院。电子邮箱:vividfish.danwei@gmail.com。 ［文摘］北极地区目前尚存的海洋划界争端主要是巴伦支海(挪威vs.俄罗斯)和波弗特海(加拿大vs.美国)。①除此以外,目前最热议的无疑是北极航道的法律地位问题。随着全球气候变暖,北极海冰加速融化,一些科学家乐观预测,在未来30年内北冰洋将出现夏季无冰年,使北冰洋“黄金水道”开通成为可能。本文尝试对北极航道的法律地位进行研究,在国内外学者的研究基础上,将 西北航道分为航线S和航线N,北方海航道分为极地航线、高纬度航线、中央航线和滨海航线,提出不能将北极航道的法律地位单一化,不同航线应具有不同的法律地位。［Abstract］The most striking Arctic maritime delimitation dispute,in addition to the surviving controversies of the Barents Sea(Norway vs.Russia) and the Beaufort Sea(Canada vs. the United States),is undoubtedly the legal status of the Arctic Navigation Routes (ANR).①In light of the accelerated melting of Arctic sea ice with global warming,some scientists have optimistically forecasted that ice-free summer might occur within the next thirty years,which would make it possible to open a golden waterway in the Arctic Ocean.Based on the research of scholars in China and abroad,this paper,by dividing the Northwest Passage (NWP) into Route S and Route N,and the Northern Sea Route (NSR) into the Polar Route,the High-latitude Route,the Central Route,and the Coastal Route,attempts to present the idea that the legal status of ANR is not one-folded,and that different routes have different legal status.